Evaluation of the Implementation of Li-Fi in the Communes of Santiago - Viera-Riquelme, E; Gonzalez-Ortega, A; Astudillo-Muñoz, G (Springer Science and Business Media Deutschland GmbH, 2020)
This work seeks to implement the functioning of a network communication system, this is done through visible light in the urban sectors of the metropolitan region. While it should be known that, Li-Fi (Light Fidelity) is a wireless communication system that uses visible light as a means of data propagation, becoming an alternative to wireless radio frequency systems. The multicriteria method called Elimination et Choix Traduisant la Réalité (ELECTRE). An extended version of ELECTRE I method will be used to obtain a reliable result, since it is possible to obtain a decision with several alternatives, deriving a single solution from the analysis. It must be taken into account that the election process is about the correct place to implement Li-Fi connections, taking into account as a dependent variable places with a better standard of living in the Metropolitan Region, and random variables will be about areas of interest such as; physical, climatological, among others. Likewise, it must be borne in mind that the advantages, disadvantages and hierarchy are evaluated in order of preference. © 2020, Springer Nature Switzerland AG.
Keywords: ELECTRE I; Li-Fi; VLC